Stress and quality of life among education professionals in Brazil - a review / Estresse e qualidade de vida entre profissionais da educação no Brasil - uma revisão - Izael Moreno de Oliveira Júnior; Iverson Lucas Oliveira da Silva; Iverson Lucas Oliveira da Silva; Jakelline Raposo (Universidade Estadual de Alagoas, 2019)
Stress can affect the health of the worker, since it consists of a psychophysiological condition that involves several situations in which the individual feels exposed to real or imaginary threats. This situation can also negatively affect the quality of life in the work environment. The aim of this research was to make a survey about research on stress and quality of life among education professionals. This is an integrative review of the literature carried out in the period of August and September of 2018, in the databases Scielo and Virtual Health Library, using the key words: "stress"; "occupational stress"; "psychological stress"; "teachers"; "academic"; "quality of life"; "works"; "teachers"; " technicians". the filters available in the databases and the articles were analyzed and selected were used initially by title, abstract and by reading the full article. Duplicate articles were excluded and did not address the research topic. After analysis, six articles composed the final sample. The surveys were concentrated in the teaching profession in primary education and in southern Brazil. Stress and quality of life were evaluated in most of the studies using the indicators of Burnout Syndrome. The studies analyzed showed the shortage of research on technical and support professionals working in the area of education, as well as the lack of research in the North and Central-West regions. Stress was evaluated in different ways, but with impacts on aspects of quality of life.